Administrative and legal support for the management of integrated economic structures in a globalized business processes - Ненько, Сергій Сергійович; Ненько, С. С.; Ненько, Сергей Сергеевич; Nenko, Serhii S.; Тюхтенко, Наталія Анатоліївна; Тюхтенко, Н. А.; Тюхтенко, Наталия Анатольевна; Tiukhtenko, Nataliia A.; Краснопольська, Тетяна Миколаївна; Краснопольська, Т. М.; Краснопольская, Татьяна Николаевна; Krasnopolska, Тetiana М. (Baltija Publishing, 2021)
The subject of the study are organizational and economic relations arising in the process of administrative and legal support of management of integrated economic structures in a globalized business processes. Methodology. Instrumental and methodological apparatus of the study consists of the applied methods of organizational economic analysis, statistical methods, sample observation, economic and mathematical modeling method, grouping, generalization, expert evaluations, methods of economic theory, marketing, etc. The aim of the article is to study the basics of administrative and legal support of integrated economic structures management in the globalization of business processes. The results of the study consist in the development of specific provisions and recommendations aimed at improving the management of the formation and integrated economic structures functioning in the context of business processes globalization. The proposed recommendations will improve the level of administrative and legal support of corporate governance and efficiency of companies' groups. Conclusion. The following conditions of effective management of integrated economic structures in the context of business processes globalization are highlighted: compliance with the target unity in the activities of integrated economic entities; orientation of participants to achieve a synergetic effect of integration interaction; creation and maintenance of economic motivation for joint activities; orientation to reduce corporate risks of integration interaction; compatibility of resource potentials of the main interacting organizations; ensuring the controllability of integration interaction processes in the interests of the owner. Organization of rational economic relations within them and with external structures is of great importance to improve the efficiency of economic activities of integrated economic structures. These are relations with public authorities (GR-management), suppliers and customers, banks, insurance organizations, employees of enterprises, owners. The effectiveness of the group of companies largely depends on the availability and level of system development of internal regulatory management of consolidated finances. The purpose of internal regulations system is to fill gaps in the norms of existing administrative and legal legislation in the regulation of economic, managerial and financial activities of integrated economic structures.

Предметом дослідження є організаційно-економічні відносини, що виникають у процесі адміністративно-правового забезпечення управління інтегрованими економічними структурами в умовах глобалізованих бізнес-процесів. Методологія. Інструментально-методичний апарат дослідження складається з застосовуваних методів організаційно-економічного аналізу, статистичних методів, вибіркового спостереження, методу економіко-математичного моделювання, групування, узагальнення, експертних оцінок, методів економічної теорії, маркетингу тощо. Мета статті полягає у вивченні основ адміністративно-правового забезпечення управління інтегрованими економічними структурами в умовах глобалізації бізнес-процесів. Результати дослідження полягають у розробці конкретних положень та рекомендацій, спрямованих на вдосконалення управління формуванням та інтегрованими економічними структурами, що функціонують в умовах глобалізації бізнес-процесів. Запропоновані рекомендації підвищать рівень адміністративно-правового забезпечення корпоративного управління та ефективність діяльності груп компаній. Висновок. Виокремлено такі умови ефективного управління інтегрованими економічними структурами в умовах глобалізації бізнес-процесів: дотримання цільової єдності в діяльності об’єднаних суб’єктів господарювання; орієнтація учасників на досягнення синергетичного ефекту інтеграційної взаємодії; створення та підтримання економічної мотивації до спільної діяльності; орієнтація на зниження корпоративних ризиків інтеграційної взаємодії; сумісність ресурсних потенціалів основних взаємодіючих організацій; забезпечення керованості процесів інтеграційної взаємодії в інтересах власника. Велике значення для підвищення ефективності господарської діяльності інтегрованих господарських структур має організація раціональних економічних зв'язків всередині них і із зовнішніми структурами. Це відносини з органами державної влади (GR-менеджмент), постачальниками та замовниками, банками, страховими організаціями, працівниками підприємств, власниками. Ефективність діяльності групи компаній значною мірою залежить від наявності та рівня розвитку системи внутрішнього нормативного управління консолідованими фінансами. Метою системи внутрішнього розпорядку є заповнення прогалин у нормах чинного адміністративно-правового законодавства в регулюванні господарської, управлінської та фінансової діяльності об'єднаних господарських структур.
Nenko S. Administrative and legal support for the management of integrated economic structures in a globalized business processes / S. Nenko, N. Tyukhtenko, T. Krasnopolska // Baltic journal of economic studies. - Vol. 7. - Iss. 4. - Baltija Publishing, 2021. - P. 145-152.
Keywords: administrative and legal support; macroeconomic policy; globalization; business processes; management; GR-management; economy; integrated economic structures; competitiveness; production efficiency; international market; administrative law; адміністративно-правове забезпечення; макроекономічна політика; глобалізація; бізнес-процеси; менеджмент; GR-менеджмент; економіка; інтегровані економічні структури; конкурентоспроможність; ефективність виробництва; міжнародний ринок; адміністративне право; Research Subject Categories::LAW/JURISPRUDENCE